International Child Abduction in the European Union: the Solutions Incorporated by the Council Regulation - Ballesteros, Mónica (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2004)
This paper analyzes the new regulation developed in the European Union aimed at international child abductions. The Hague Convention of 25 October, 1980 on the Civil Aspects of International Child Abduction is the instrument that authorities of the contracting States were using to decide about the restitution of the child. The main focus of this article will firstly, study how the Hague Convention of 25 October, 1980 on the Civil Aspects of International Child Abduction is going to be put into practice with the Council Regulation (EC) N° 2201/2003; subsequently try to see which are the modifications in the new Community law in relation to the Council Regulation (EC) N° 1347/2000; and finally, we will examine the innovations included in the new Council Regulation.